Nepal : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report, 2019)
This Article IV Consultation highlights that following a prolonged period of tepid growth, economic activity in Nepal has picked up, reflecting cyclical factors and some structural improvements, especially in electricity supply. Discussions focused on policies needed to stem rising balance of payments pressures, safeguard financial stability, and structural reforms to ensure high, sustainable and inclusive growth. Continued improvements in revenue performance are seen to be important to maintain a strong fiscal position and meet capital spending needs. The IMF staff welcomed the authorities' efforts to increase domestic revenue mobilization. The authorities broadly agreed with the IMF staff's assessment and fiscal policy advice. The authorities noted that the transition to fiscal federalism and the pickup of reconstruction. Progress has been made with putting in place a fiscal federal framework but more needs to be done to ensure sustainability, make budgets more realistic and spending more efficient, and build implementation capacity.